A COMPREHENSIVE REVIEW OF NANO-FERTILIZERS: THEIR ROLE IN ENHANCING AGRICULTURAL PRODUCTIVITY AND IMPACTS ON ANIMALS AND SOIL MICROBIOTA - ANINDITA DEKA; SANKRANTI DEVI; RIYA MAZUMDAR; ATLANTA KALITA; PRACHUJYA GOGOI; SOUJIT KUMAR; TANMEE DEORI; BINOY SHARMA; HEENA THAKURIA (The Bioscan, 2025)
Nano-fertilizers have the potential to meet plant nutrition needs, increase farmer profitability, and promote sustainable crop production without sacrificing yields Nano fertilizers effectively regulate nutrients in precision agriculture by matching crop growth stages and providing nutrients throughout the growth period.Nanofertilizers improve the surface area available to various metabolic processes in the plant, accelerating photosynthesis and increasing crop yield and dry matter production.Nanofertilizers effectively regulate nutrients in precisionagriculture by matching crop growth stages and providing nutrients throughout the growth period. Nanofertilizers boost crop growth up to the optimal concentrations. Increased fertilizer concentrations can harm crop growth due to toxicity.By using techniques like targeted delivery, slow/controlled release, and conditional release, nanostructured formulations could more precisely release their active ingredients in response to biological demands and environmental cues.Research indicates that the utilization of nanofertilizers improves the efficiency of nutrient utilization, lowers soil toxicity, limits the possible adverse effects of excessive dose, and decreases the frequency of application.Along with providing valuable information about the introduction of various nanoparticle forms in the agricultural industry, the research would help pave the way for a new path toward the nano-revolution. This review highlights the challenges of current agricultural practices, the properties and applications of nano-fertilizers, and their contribution to the development of sustainable agricultural methods, synthesis of nanoparticles, effect of nano-fertilizers on seed germination, animals, soil microorganisms, etc., and toxicology followed by crop plants morph-physiological alternation after exposure to nano- fertilizers. It provides a foundation for future research into their effective and responsible use in agriculture.